DETERMINANTS OF NURSES’ DISASTER PREPAREDNESS IN FLOOD PRONE AREAS: APPLICATION OF PROTECTION MOTIVATION THEORY - Chasanah, Nur Rofiqoh; Kurniawati, Ninuk Dian; Tristiana, Rr Dian (Universitas Airlangga, 2025)
Background: Floods are among Indonesia’s most frequent and destructive natural disasters, posing serious threats to public health and service continuity. Nurses in community health centers play a critical role in disaster preparedness, especially in flood-prone regions. Guided by the Protection Motivation Theory (PMT), this study examined the relationships among response efficacy, self-efficacy, response cost, motivation, and disaster preparedness among nurses in flood-prone areas of Gresik District. Methods: A cross-sectional correlational study was conducted among 78 nurses selected through proportionate random sampling from flood-prone community health centers. Inclusion criteria were at least one year of work experience and voluntary participation. Data were collected using validated self-administered questionnaires based on PMT constructs: response efficacy (10 items), self-efficacy (10 items), response cost (8 items), motivation (10 items), and disaster preparedness (12 items), rated on a 5-point Likert scale. Reliability coefficients were acceptable (Cronbach’s α = 0.76–0.89). Data were analyzed using descriptive statistics and Spearman’s rho correlation tests. Results: Most nurses demonstrated high disaster preparedness. Response efficacy (ρ = 0.000; r = 0.470) and self efficacy (ρ = 0.011; r = 0.287) were positively correlated with motivation, whereas response cost (ρ = 0.000; r = –0.438) was negatively correlated. Motivation also showed a significant positive relationship with disaster preparedness (ρ = 0.000; r = 0.402). Conclusions: Response efficacy, self-efficacy, and response cost are key cognitive predictors of motivation influencing nurses’ disaster preparedness. Strengthening motivation through education, simulation-based training, and organizational support can enhance preparedness, patient safety, and healthcare quality during flood emergencies.